Small-angle neutron scattering and magnetically heterogeneous state in Sr2FeMoO6–δ - Kalanda, Nikolay (2019)
Single-phase strontium ferromolybdate (Sr2FeMoO6–δ) samples with different degrees of the superstructural ordering of the Fe/Mo cations were obtained from partially reduced SrFeO3–х, SrMoO4 precursors by the solid-state technology. The study of the temperature dependences of the magnetization measured in the field-cooling and zero-field-cooling regimes indicated an inhomogeneous magnetic state of the samples. The presence of magnetic regions of different nature has also been revealed by the small-angle neutron scattering. For the Sr2FeMoO6–δ samples with different superstructural ordering of the Fe/Mo cations and for all values of the magnetic field induction in the range up to 1.5 T and of the scattering vector in the interval 0.1 >q >0.005 Å–1, the analytical dependence I ~ q–α obeys the Porod law (α ≈ 4), which corresponds to an object with a smooth and well-marked surface and polydisperse grain size. Deviations from the Porod law in the q > 0.1 Å–1 region and a weakening of the neutron scattering in applied magnetic fields may be ascribed to magnetic inhomogeneities with diameters D <6 nm, which are partially destroyed /oriented by magnetic fields В ≥1.5 T.